2022
DOI: 10.1155/2022/9928362
|View full text |Cite
|
Sign up to set email alerts
|

The Ecto-5 nucleotidase/CD73 Mediates Leishmania amazonensis Survival in Macrophages

Abstract: Endogenous nucleotides produced by various group of cells under inflammatory conditions act as potential danger signals in vivo. Extracellularly released nucleotides such as ATP are rapidly hydrolyzed to adenosine by the coordinated ectonucleotidase activities of CD39 and CD73. Leishmania is an obligate intracellular parasite of macrophages and capable of modulating host immune response in order to survive and multiply within host cells. In this study, the activity of CD73 induced by Leishmania amazonensis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that CD73 is associated with bacterial escape, enhancing neutrophil recruitment during Mycobacterium tuberculosis infection (Dubois-Colas et al, 2014;Petit-Jentreau et al, 2015). CD73 is crucial for reducing tissue damage and controlling Toxoplasma gondii infection (Yilmaz et al, 2017), and it increases L. amazonensis survival via immunomodulatory effects activated by adenosine receptors (Basu et al, 2020;Bajracharya et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CD73 is associated with bacterial escape, enhancing neutrophil recruitment during Mycobacterium tuberculosis infection (Dubois-Colas et al, 2014;Petit-Jentreau et al, 2015). CD73 is crucial for reducing tissue damage and controlling Toxoplasma gondii infection (Yilmaz et al, 2017), and it increases L. amazonensis survival via immunomodulatory effects activated by adenosine receptors (Basu et al, 2020;Bajracharya et al, 2022).…”
Section: Discussionmentioning
confidence: 99%